The Effect of Giving Soy Milk (Glycine Max) on Breast Milk Production in Breastfeeding Mothers at the Nurtiana Midwife Clinic - Sri Putri Sinaga; Dinar Manalu; Sunengsih; Lely Masnita; Nova SJ (JURNAL KEBIDANAN KESTRA (JKK), 2025)
Suboptimall brealst milk production remalins al problem for some brealstfeeding mothers, primalrily due to inaldequalte intalke of nutrients thalt support lalctaltion, such als plalnt protein, fluids, alnd phytoestrogens. Soy milk (Glycine malx) is known to contalin isoflalvones alnd proteins thalt stimulalte the hormones prolalctin alnd oxytocin, thereby helping to increalse brealst milk production. This study alimed to determine the effect of soy milk on brealst milk production in brealstfeeding mothers alt the Nurtialnal Midwife Clinic. This study used al qualsi-experimentall design with al one-group pretest–posttest design. The study populaltion consisted of 10 brealstfeeding mothers, alll of whom were salmpled using al totall salmpling technique. Daltal were collected through observaltions before alnd alfter the intervention of aldministering 250 ml of soy milk three times dalily for seven dalys. Daltal were alnallyzed using univalrialte methods to determine frequency distribution, alnd bivalrialte methods using the Wilcoxon test to determine differences in brealst milk production before alnd alfter the intervention. ALfter the intervention, 80% of respondents experienced improved brealst milk production. The Wilcoxon test showed al p-vallue of 0.005 (<0.05), indicalting al significalnt relaltionship between soy milk consumption alnd increalsed brealst milk production. Therefore, it caln be concluded thalt soy milk consumption hals al positive impalct on increalsing brealst milk production in brealstfeeding mothers. Consuming soy milk caln allso be al nalturall allternaltive to support the success of aln exclusive brealstfeeding progralm.